AN ANALYSIS TRANSLATION OF WORD FORMATION FROM ENGLISH INTO INDONESIAN ON PRINCIPLES OF LANGUAGE LEARNING AND TEACHING - Sholihin; M. Yani (STKIP Taman Siswa Bima, 2017)
There are some unproffesional translators in Indonesia. It can be proved that there are some translator are not capable enough in the source and target language and in the technique of the translation. In addition there are some translation works from indonesian into English still uses Indonesian structure. So, it can be said that the quality of the translation, especially from English into Indonesian is still questionable and unsatisfactory. The wise solution for many problems presented above is translation. Translation is the process of replacement’s meaning, message and style from one Language to another in the written form. One of the translation theories should be known by the translator is words formation. Words formation is the the way used by the translator in translating the language. The finding of this study shows that the translator uses three process on principles of language learning and teaching book. Those prosedures are derivation, compounding and acronyms. Then, almost of all process used by the translators are words formation. These inappropriateness sentence involve the structure or the grammar of the sentence.The researcher suggest to the next researcher to conduct the words formation in another object.